A study of elopement among muslims in Malaysia and Island of Lombok, Indonesia (Kajian “Kahwin Lari” dalam Kalangan Muslim di Malaysia dan Pulau Lombok, Indonesia) - Md Said, Muhamad Helmi; Md Hashim, Noraini; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina (UKM Press, Universiti Kebangsaan Malaysia, 2018)
The phenomenon of marriage by way of elopement captures the attention of many in Malaysia in recent years. The practice which is locally termed as ‘kahwin lari’ is known to cause serious problems to the couples and their families as it usually contracted between couples having difficulty to get consent from their families. In contrast, such marriages are customarily practiced in the Lombok Island of Indonesia. While such practice, locally known as ‘merariq’ is legal and approved by the custom of the inhabitants of the Island, the same practice is illegal and it entails legal consequences under the Malaysian criminal law. This prompts urgent needs to address such problems in order to come out with possible solutions in the form of policies. Thus it is important to look into and research the legal and customary practices of kahwin lari in the Island and in Malaysia as is the aim of this paper. This research is designed for socio-legal study and uses qualitative method. Data is obtained through informants consisting of the religious and customary leaders, officers from religious office as well as couples who practiced and experienced kahwin lari. This article is a preamble to a more detailed study of the cross border marriages where the result will be useful for further improvement of the existing legal provisions on kahwin lari in Malaysia.